Low-carbon cement concrete steam curing enhancer and application thereof
By using low-carb cement concrete vaporization enhancer in high-iron phase cement clinker, combined with the combination of nano calcium carbonate, alcohol amine additives, inorganic salts and surfactants, the problem of decreasing concrete strength under the vaporization process is solved, and the effect of efficiently improving the early and final strength of concrete is achieved.
Patent Information
- Application Number
- CN202510113886.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The existing concrete reinforcement agent cannot effectively improve the early and final strength of high-speed iron phase cement clinker under the steaming and curing process, which may instead lead to a decrease in strength.
A low-carb cement concrete vaporization enhancer is used, which consists of nano calcium carbonate, alcohol amine additive, inorganic salt and surfactant. By adjusting the standstill time and ratio, the strength reduction problem caused by the combination of alcohol amine enhancer and vaporization technology is reversed.
This reinforcement can quickly improve the early and final strength of concrete components, ensure that the strength of high-speed rail-phase cement concrete components can reach 24.5MPa in 3 days, solving the problem of strength reduction under the steaming and cooking process.
Smart Images

Figure BDA0005257336770000031 
Figure BDA0005257336770000051 
Figure BDA0005257336770000061
Abstract
Description
Technical Field
[0001] The invention relates to a concrete reinforcing agent and application thereof, in particular to a low-carbon cement concrete steam-curing reinforcing agent and application thereof in concrete steam-curing preparation. Background Art
[0002] Compared with ordinary Portland cement clinker, high iron phase cement clinker can reduce carbon dioxide emissions during the firing process and achieve low-carbon energy-saving effects. However, if the iron phase in high iron phase cement clinker is too high, the early strength of the clinker will be reduced.
[0003] Steam curing, also known as steam curing, can improve the early strength of concrete components. Steam curing is to pre-cure the poured concrete components in saturated steam at a relative humidity of more than 90% and 60-80°C for 5-8 hours. Usually, the early strength of concrete can be quickly improved after steam curing.
[0004] Adding concrete strengtheners during the cement clinker forming process can effectively improve the early strength of cement clinker, but existing strengtheners (such as some amine substances, inorganic salts, etc.) are not suitable for steam curing process. After these strengtheners are added to cement clinker under steam curing conditions, the early and final strength of concrete will decrease. Therefore, how to screen and obtain a strengthener composition for preparing high-strength concrete by steam curing of high-iron phase cement clinker has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a low-carbon cement concrete steam curing enhancer to solve the problem of how to improve the strength of concrete under the steam curing process. Another purpose of the present invention is to propose an application of a low-carbon cement concrete steam curing enhancer in concrete steam curing preparation to solve the problem of how to prepare concrete components by steam curing.
[0006] Technical solution: The low-carbon cement concrete steam-curing enhancer described in the present invention comprises the following components in parts by weight: 0.5-5 parts of nano-calcium carbonate, 0.02-0.2 parts of alcohol amine additives, 0-2 parts of inorganic salts, and 0.01-0.2 parts of surfactants; the alcohol amine additive comprises at least one of diethanol monoisopropanolamine, monoethanol diisopropanolamine, triethanolamine, and triisopropanolamine; the inorganic salt comprises at least one of aluminum sulfate, sodium aluminate, sodium chloride, sodium sulfate, and calcium chloride; and the surfactant comprises at least one of polydimethylsiloxane, fluorosilicone, and ethylene glycol siloxane.
[0007] In some embodiments, the concrete steam curing enhancer comprises the following components in parts by weight: 0.08-0.3 parts of aluminum sulfate, 0.02-0.06 parts of alcohol amine additives, and 0-0.03 parts of sodium chloride; the alcohol amine additives are composed of 0.01-0.03 parts of diethanol monoisopropanolamine and 0.01-0.03 parts of monoethanol diisopropanolamine;
[0008] In some embodiments, the concrete steam curing enhancer comprises the following components in parts by weight: 0.08-0.3 parts of sodium aluminate, 0.02-0.06 parts of an alcoholamine additive, and 0-0.03 parts of sodium chloride; the alcoholamine additive is composed of 0.01-0.03 parts of diethanol monoisopropanolamine and 0.01-0.03 parts of monoethanol diisopropanolamine;
[0009] In some embodiments, the concrete steam curing enhancer comprises the following components in parts by weight: 0.02-0.06 parts of an alcohol amine additive, 0.03 parts of sodium chloride; the alcohol amine additive is composed of 0.01-0.03 parts of diethanol monoisopropanolamine and 0.01-0.03 parts of monoethanol diisopropanolamine;
[0010] In some embodiments, the concrete steam curing enhancer comprises the following components in parts by weight: 0.08-0.3 parts of aluminum sulfate, 0.03 parts of triethanolamine, and 0.03 parts of sodium chloride.
[0011] The present invention further uses the above-mentioned low-carbon cement concrete steam curing enhancer to prepare concrete steam curing, and the specific method includes the following steps:
[0012] (1) dissolving an olamine additive, an inorganic salt, and a surfactant in water to obtain a strengthening solution;
[0013] (2) Grinding gypsum, limestone powder and cement clinker together to obtain cement, mixing cement, nano calcium carbonate and aggregate evenly, adding reinforcing liquid and mixing to obtain concrete or mortar;
[0014] (3) After the concrete is formed, it is allowed to stand and undergo standard curing, followed by steam curing, and then standard curing and water curing are performed in sequence to obtain a concrete component.
[0015] Preferably, in step (1), the enhancement solution contains diethanol monoisopropanolamine with a final concentration of 0.025-0.05wt%, monoethanol diisopropanolamine with a final concentration of 0.025-0.05wt%, aluminum sulfate with a final concentration of 0.2-0.5wt%, sodium aluminate with a final concentration of 0.2-0.5wt%, and fluorosilicone with a final concentration of 0.01-0.25wt%;
[0016] Or the enhancement solution contains sodium chloride with a final concentration of 0.01-0.05wt%, diethanol monoisopropanolamine with a final concentration of 0.025-0.05wt%, monoethanol diisopropanolamine with a final concentration of 0.025-0.05wt%, and fluorosilicone with a final concentration of 0.01-0.25wt%;
[0017] Or the enhancement solution contains triethanolamine with a final concentration of 0.025-0.05wt%, aluminum sulfate with a final concentration of 0.2-0.5wt%, sodium chloride with a final concentration of 0.01-0.05wt%, and fluorosilicone with a final concentration of 0.01-0.25wt%.
[0018] Preferably, in step (2), the cement clinker contains at least 60 wt% of high iron phase cement clinker.
[0019] Preferably, in step (2), the cement clinker consists of 0-30 parts by weight of Portland cement clinker and 60-90 parts by weight of high iron phase cement clinker.
[0020] Preferably, the components of the high iron phase cement clinker are:
[0021] C3A≤1.5wt%, 19.0±1.0wt%C4AF, 53.0±1.0wt%C3S, 23.0±1.0wt%C2S, KH
[0022] 0.880±0.01, SM is 2.10±0.10, and IM is 0.70±0.10.
[0023] Preferably, in step (2), the mass ratio of gypsum: limestone: cement clinker is 3-7: 3-7: 86-94; when preparing concrete or mortar, the mass ratio of reinforcing liquid: nano calcium carbonate: cement: aggregate is 100-270: 5-50: 250-500: 900-2000.
[0024] Preferably, in step (3), the standing time is 1-4 hours; and the steaming treatment condition is heating to 80-90° C. and steaming for 2-8 hours.
[0025] Preferably, the method of standard curing and water curing is standard curing for 24 hours and then water curing for 28 days.
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0027] The present invention screens out a reinforcing agent for high-iron phase cement clinker, and the reinforcing agent can be adapted to the steam curing process to quickly improve the early strength and final strength of concrete components.
[0028] The present invention reverses the strength reduction problem caused by the combined use of an amine-type enhancer and a steam-curing process by adjusting the standing time and the ratio before steam-curing, so that the enhancer and the steam-curing process produce a synergistic effect. The high-iron phase cement concrete component prepared by the present invention has a strength of up to 24.5 MPa after 3 days. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below.
[0030] Example 1: A low-carbon cement concrete steam curing enhancer, comprising the following components in parts by weight: 20 parts of nano-calcium carbonate, 0.08 parts of aluminum sulfate, 0.08 parts of sodium aluminate, 0.01 parts of diethanol monoisopropanolamine, 0.01 parts of monoethanol diisopropanolamine, and 0.01 parts of fluorosilicone;
[0031] The above reinforcing agent is used to prepare a concrete component, and the method is as follows:
[0032] (1) dissolving aluminum sulfate, sodium aluminate, diethanol monoisopropanolamine, monoethanol diisopropanolamine, and fluorosilicone in water to obtain a reinforcing solution, wherein the final concentration of diethanol monoisopropanolamine in the reinforcing solution is 0.025 wt %, the final concentration of monoethanol diisopropanolamine is 0.025 wt %, the final concentration of aluminum sulfate is 0.2 wt %, the final concentration of sodium aluminate is 0.2 wt %, and the final concentration of fluorosilicone is 0.025 wt %;
[0033] (2) Gypsum, limestone powder and cement clinker are ground together in a mass ratio of 5:5:90 to obtain cement, 375 parts by weight of cement, 20 parts by weight of nano calcium carbonate and 1000 parts by weight of standard sand are uniformly mixed, and then 150 parts by weight of reinforcing liquid are added and mixed to obtain mortar; the cement clinker is all high-iron phase cement clinker, and the composition of the high-iron phase cement clinker is as follows:
[0034]
[0035] (3) After the mortar is poured into the mold and formed, it is allowed to stand in a standard curing box for 2 hours, and then moved to a steam curing equipment for steam curing with the mold. The steam curing conditions are to heat the temperature to 90°C and steam cure for 4 hours. After the steam curing is completed, standard curing is performed for 24 hours, and then water curing is performed for 28 days to obtain a mortar specimen.
[0036] Example 2: A low-carbon cement concrete steam-curing enhancer, comprising the following components in parts by weight: 0.5 parts of nano-calcium carbonate, 0.3 parts of aluminum sulfate, 0.3 parts of sodium aluminate, 0.03 parts of diethanol monoisopropanolamine, 0.03 parts of monoethanol diisopropanolamine, and 0.01 parts of ethylene glycol siloxane;
[0037] The above reinforcing agent is used to prepare a concrete component, and the method is as follows:
[0038] (1) dissolving aluminum sulfate, sodium aluminate, diethanol monoisopropanolamine, and monoethanol diisopropanolamine in water to obtain a reinforcing solution, wherein the final concentration of diethanol monoisopropanolamine in the reinforcing solution is 0.05 wt %, the final concentration of monoethanol diisopropanolamine is 0.05 wt %, the final concentration of aluminum sulfate is 0.5 wt %, the final concentration of sodium aluminate is 0.5 wt %, and the final concentration of ethylene glycol siloxane is 0.017 wt %;
[0039] (2) Gypsum, limestone powder and cement clinker are ground together in a mass ratio of 3:3:94 to obtain cement; 25 parts by weight of cement, 0.5 parts by weight of nano-calcium carbonate and 90 parts by weight of standard sand are uniformly mixed, and then 10 parts by weight of reinforcing liquid are added and mixed to obtain mortar; the cement clinker is composed of 60 parts by weight of high-iron phase cement clinker and 30 parts by weight of ordinary Portland cement clinker, and the high-iron phase cement clinker is the same as in Example 1.
[0040] (3) After the concrete colloid is poured into the mold for forming, it is allowed to stand in a standard curing box for 4 hours, and then moved to a steam curing equipment for steam curing with the mold. The steam curing conditions are to heat the temperature to 80°C and steam cure for 2 hours. After the steam curing is completed, standard curing is performed for 24 hours, and then water curing is performed for 28 days to obtain a concrete component.
[0041] Example 3: A low-carbon cement concrete steam curing enhancer, comprising the following components in parts by weight: 50 parts of nano-calcium carbonate, 0.025 parts of sodium chloride, 0.0125 parts of diethanol monoisopropanolamine, 0.0125 parts of monoethanol diisopropanolamine, and 0.125 parts of polydimethylsiloxane;
[0042] The above reinforcing agent is used to prepare a concrete component, and the method is as follows:
[0043] (1) dissolving sodium chloride, diethanol monoisopropanolamine, and monoethanol diisopropanolamine in water to obtain an enhancement solution, wherein the final concentration of diethanol monoisopropanolamine in the enhancement solution is 0.025 wt %, the final concentration of monoethanol diisopropanolamine is 0.025 wt %, the final concentration of sodium chloride is 0.05 wt %, and the final concentration of polydimethylsiloxane is 0.25 wt %;
[0044] (2) Gypsum, limestone powder and cement clinker are ground together in a mass ratio of 7:7:86 to obtain cement; 500 parts by weight of cement, 50 parts by weight of nano-calcium carbonate and 2000 parts by weight of standard sand are uniformly mixed; and then 270 parts by weight of reinforcing liquid are added and mixed to obtain mortar; the cement clinker is all high-iron phase cement clinker, and the high-iron phase cement clinker is the same as in Example 1.
[0045] (3) After the concrete colloid is poured into the mold for forming, it is allowed to stand in a standard curing box for 1 hour, and then moved to a steam curing equipment for steam curing with the mold. The steam curing conditions are to heat the temperature to 85°C and steam cure for 3 hours. After the steam curing is completed, standard curing is performed for 24 hours, and then water curing is performed for 28 days to obtain a concrete component.
[0046] Embodiment 4: All other aspects are the same as Embodiment 1, except that:
[0047] The enhancement solution contains triethanolamine with a final concentration of 0.05 wt %, aluminum sulfate with a final concentration of 0.2 wt %, sodium chloride with a final concentration of 0.01 wt %, and fluorosilicone with a final concentration of 0.05 wt %. The amount of the enhancement solution used is 200 parts by weight.
[0048] The cement clinker consists of 80 parts by weight of high iron phase cement clinker and 10 parts by weight of ordinary Portland cement clinker.
[0049] Embodiment 5: The rest is the same as Embodiment 1, except that:
[0050] Taking the standing time in step (3) as a variable, four time gradients of 0, 1, 2, and 4 h were set to prepare different concrete components respectively.
[0051] Comparative Example 1: The rest is the same as Example 1, except that:
[0052] After the mortar is poured into the mold and formed, it is not allowed to stand or steam for treatment. It is directly subjected to standard curing at 20°C for 24 hours, and then water-cured for 28 days to obtain the mortar test block.
[0053] Comparative Example 2: The rest is the same as Example 5, except that:
[0054] Replace high iron phase cement clinker with ordinary Portland cement clinker.
[0055] Comparative Example 3: The rest is the same as Example 1, except that:
[0056] Replace high iron phase cement clinker with ordinary Portland cement clinker.
[0057] After the mortar is poured into the mold and formed, it is not allowed to stand or steam for treatment. It is directly subjected to standard curing at 20°C for 24 hours, and then water-cured for 28 days to obtain the mortar test block.
[0058] Comparative Example 4: The rest is the same as Example 5, except that:
[0059] The high iron phase cement clinker is replaced with a mixed clinker of 60 parts by weight of high iron phase cement clinker and 30 parts by weight of ordinary Portland cement clinker.
[0060] Comparative Example 5: The rest is the same as Example 1, except that:
[0061] The high iron phase cement clinker is replaced with a mixed clinker of 60 parts by weight of high iron phase cement clinker and 30 parts by weight of ordinary Portland cement clinker.
[0062] After the mortar is poured into the mold and formed, it is not allowed to stand or steam for treatment. It is directly subjected to standard curing at 20°C for 24 hours, and then water-cured for 28 days to obtain the mortar test block.
[0063] Comparative Example 6: The rest is the same as Example 1, except that no reinforcing agent is added.
[0064] Comparative Example 7: The rest is the same as Example 1, except that the enhancer does not contain an alcoholamine enhancer, and contains the following components in parts by weight: 5 parts of nano-calcium carbonate, 0.08 parts of aluminum sulfate, and 0.01 parts of fluorosilicone. The final concentration of fluorosilicone is 0.2wt%.
[0065] Comparative Example 8: The rest is the same as Example 1, except that: the low-carbon cement concrete steam curing enhancer does not contain nano calcium carbonate, inorganic salts and surfactants, and contains the following components in parts by weight: 0.01 parts of diethanol monoisopropanolamine and 0.01 parts of monoethanol diisopropanolamine. The final concentration of diethanol monoisopropanolamine in the enhancing solution is 0.025wt%, and the final concentration of monoethanol diisopropanolamine is 0.025wt%.
[0066] Comparative Example 9: The rest is the same as Example 1, except that:
[0067] 0.01 parts of diethanol monoisopropanolamine and 0.01 parts of monoethanol diisopropanolamine were replaced with 0.02 parts of triisopropanolamine.
[0068] The flexural strength and compressive strength of the mortars prepared in Examples 1-5 and Comparative Examples 1-5 were measured on the 3rd and 28th days of curing, respectively. Each component was tested three times and the average value was taken. The results are as follows:
[0069] Table 1 Strength test results of different concrete components on the 3rd and 28th days of curing
[0070]
[0071]
[0072] In the results in Table 1, the comparison between Comparative Example 1 and the group left standing for 0 h in Example 5, the comparison between Comparative Example 3 and the group left standing for 0 h in Comparative Example 2, and the comparison between Comparative Example 5 and the group left standing for 0 h in Comparative Example 4 all show that for different cement clinkers, if steam curing is directly performed after adding the reinforcing agent, the early and final strengths will decrease. The combination of the reinforcing agent and the steam curing process not only fails to improve the strength of the concrete, but significantly reduces the strength of the concrete.
[0073] However, Example 5, Comparative Example 2 and Comparative Example 4 show that the strength reduction problem caused by the combined use of the reinforcing agent and steam curing can be reversed by prolonging the standing time, and the reinforcing agent and steam curing treatment can synergistically improve the early strength and final strength of the concrete, and the effect is better for high-iron phase cement clinker or mixed clinker containing high-iron phase cement clinker.
[0074] In addition, Comparative Example 6 shows that when no reinforcing agent is added, the early and late strengths of the high iron phase low carbon cement under the steam curing rapid curing conditions decrease significantly, affecting the application effect of the cement. Comparative Examples 7 and 8 show that when amine and other components are added separately, the early or late strength of the steam curing specimens can be slightly improved, but the effect is significantly lower than that of co-addition.
[0075] In addition, Comparative Example 9 shows that the type of alcoholamine additives has a key influence on the effect of the reinforcing agent, and the wrong choice of alcoholamine substances will affect the strength of concrete under steam curing conditions.
Claims
1. A low carbon cement concrete steam curing enhancer, characterized in that: The invention comprises the following components in parts by weight: 0.5-5 parts of nano-calcium carbonate, 0.02-0.2 parts of alcoholamine additive, 0-2 parts of inorganic salt, and 0.01-0.2 parts of surfactant; the alcoholamine additive comprises at least one of diethanol monoisopropanolamine, monoethanol diisopropanolamine, triethanolamine, and triisopropanolamine; the inorganic salt comprises at least one of aluminum sulfate, sodium metaaluminate, sodium chloride, sodium sulfate, and calcium chloride; and the surfactant comprises at least one of polydimethylsiloxane, fluorosilicone, and ethylene glycol siloxane.
2. Use of the low-carbon cement concrete steam curing enhancer according to claim 1 in the preparation of concrete steam curing.
3. The use according to claim 2, characterized in that: The steps include: (1) dissolving an olamine additive, an inorganic salt, and a surfactant in water to obtain a strengthening solution; (2) Grinding gypsum, limestone powder and cement clinker together to obtain cement, mixing cement, nano calcium carbonate and aggregate evenly, adding reinforcing liquid and mixing to obtain concrete or mortar; (3) After the concrete is formed, it is allowed to stand and undergo standard curing, followed by steam curing, and then standard curing and water curing are performed in sequence to obtain a concrete component.
4. The use according to claim 2, characterized in that: In step (1), the enhancement solution contains diethanol monoisopropanolamine with a final concentration of 0.025-0.05wt%, monoethanol diisopropanolamine with a final concentration of 0.025-0.05wt%, aluminum sulfate with a final concentration of 0.2-0.5wt%, sodium aluminate with a final concentration of 0.2-0.5wt%, and fluorosilicone with a final concentration of 0.01-0.25wt%; Or the enhancement solution contains sodium chloride with a final concentration of 0.01-0.05wt%, diethanol monoisopropanolamine with a final concentration of 0.025-0.05wt%, monoethanol diisopropanolamine with a final concentration of 0.025-0.05wt%, and fluorosilicone with a final concentration of 0.01-0.25wt%; Or the enhancement solution contains triethanolamine with a final concentration of 0.025-0.05wt%, aluminum sulfate with a final concentration of 0.2-0.5wt%, sodium chloride with a final concentration of 0.01-0.05wt%, and fluorosilicone with a final concentration of 0.01-0.25wt%.
5. The use according to claim 2, characterized in that: In step (2), the cement clinker contains at least 60 wt% of high iron phase cement clinker.
6. The use according to claim 2, characterized in that: In step (2), the cement clinker is composed of 0-30 parts by weight of Portland cement clinker and 60-90 parts by weight of high iron phase cement clinker.
7. The use according to claim 5 or 6, characterized in that: The components of the high iron phase cement clinker are: C3A≤1.5wt%, 19.0±1.0wt% C4AF, 53.0±1.0wt% C3S, 23.0±1.0wt% C2S, KH is 0.880±0.01, SM is 2.10±0.10, and IM is 0.70±0.
10.
8. The use according to claim 2, characterized in that: In step (2), the mass ratio of gypsum: limestone: cement clinker is 3-7: 3-7: 86-94; when preparing concrete or mortar, the mass ratio of reinforcing liquid: nano calcium carbonate: cement: aggregate is 100-270: 5-50: 250-500: 900-2000.
9. The use according to claim 2, characterized in that: In step (3), the standing time is 1-4 hours; the steaming treatment condition is to heat the mixture to 80-90°C and steam for 2-8 hours.
10. The use according to claim 2, characterized in that: The method of standard curing and water curing is standard curing for 24 hours and then water curing for 28 days.
Citation Information
Patent Citations
Novel high sulfur-resistant cement
CN101037306A
Method for making steam curing cement
CN1034354A
Low-heat cement capable of efficiently utilizing industrial waste gypsum
CN105314899A
Ultra-high performance concrete and preparation method thereof
CN118047562A
Concrete reinforcing method and reinforced concrete
CN118561296A
Cited By
Reinforcing agent for 3D printed concrete
CN122647145A